Towards a gender analysis model for environmental management of ecotourism resources in Kisumu County, Kenya - Olima, Washington H.A; Gor, Christopher O.; Agong', Stephen G.; Hayombe, Patrick O.; Okotto, Lorna Grace; Mogoria, Naomi Apali (International Journal of Liberal Arts and Social Science, 2015)
This paper aimed at proposing model would help promote ecotourism through gender analysis lenses aimed at ensuring equity for both men and women in the utilization of natural resources by local communities. The results showed that more men than women are involved in the utilization of environmental resources to enhance their ecotourism activities for economic gain. In contrast women use environmental resources to fulfill domestic chores and cultural obligations without much economic returns. The paper recommended that for there to be gender equity for both men and women in the management of environmental resources, a localized and functional approach of meeting local needs should be adopted through gender analysis lenses by the relevant institutional actors involved in ecotourism. In conclusion there is gender inequality in the utilization of environmental resources and this can be corrected through development of an appropriate gender analysis framework.
Keywords: Ecotourism; Gender; Environment; Management; Resources